“Problematic” Sexual Behaviors: Clinical and Legal Aspects - Agnieszka Gloria Kamińska (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
There is a vast scientific literature on psychiatric pathologies but research on the sexual problems that secondarily accompany them is still lacking. Among the few issues which in this area still manage to overcome an evident generalized resistance of patients to treating the subject and which can be the purpose of further study, beyond the sexual dysfunctions caused by drugs and the greater risk of contracting sexually transmitted diseases (STDs) we have focused in our bibliographical research on problematic sexual behaviors (PSBs). In particular, we have examined PSBs that complicate axis 2 disorders, usually the field of dynamic psychotherapy, while with reference to axis 1 only those present in bipolar disorder, because of the fact that this last, in its “ultra-rapid” cycles, is located by some authors in the symptom spectrum of borderline personality disorders. Lastly, our in-depth analysis, with the exclusion of paraphilic disorders already nosologically well classified in the DSM-5 with code F65, focused on the still poorly defined legal implications of PSBs secondary to personality disorders (PDs), with the purpose of contributing to a greater consideration of the argument in favor of adequate legal protection of patients and health professionals involved in this particular aspect of psycho-behavioral pathologies.